2019
DOI: 10.7717/peerj.6320
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genomes of three Betulaceae species: implications for molecular phylogeny and historical biogeography

Abstract: BackgroundPrevious phylogenetic conclusions on the family Betulaceae were based on either morphological characters or traditional single loci, which may indicate some limitations. The chloroplast genome contains rich polymorphism information, which is very suitable for phylogenetic studies. Thus, we sequenced the chloroplast genome sequences of three Betulaceae species and performed multiple analyses to investigate the genome variation, resolve the phylogenetic relationships, and clarify the divergence history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 74 publications
(91 reference statements)
4
29
0
Order By: Relevance
“…When less genomic resources are available for revealing divergence hotspot regions, the oligonucleotide repeats might be utilized as a substitute for identifying polymorphic regions (Ahmed et al, 2012; Ahmad, 2014). The current study results of oligonucleotide repeats are similar to the previously reported results of Nicotiana species and other angiosperm plastome studies (Asaf et al, 2016; Yang et al, 2019). Thus, the presence of both the high divergence regions in IGS and oligonucleotide repeats suggest that these regions are suitable for the development of markers to demonstrate phylogenetics relationships.…”
Section: Discussionsupporting
confidence: 92%
“…When less genomic resources are available for revealing divergence hotspot regions, the oligonucleotide repeats might be utilized as a substitute for identifying polymorphic regions (Ahmed et al, 2012; Ahmad, 2014). The current study results of oligonucleotide repeats are similar to the previously reported results of Nicotiana species and other angiosperm plastome studies (Asaf et al, 2016; Yang et al, 2019). Thus, the presence of both the high divergence regions in IGS and oligonucleotide repeats suggest that these regions are suitable for the development of markers to demonstrate phylogenetics relationships.…”
Section: Discussionsupporting
confidence: 92%
“…The content and order of genes are highly conserved in most cp genomes (Ruhlman and Jansen 2014). Little or no recombination events are usually detected in the cp genome that also is subjected to a slow mutation rate (Yang et al 2019), although some species of the Fabaceae family, which are exceptions, have a rapid mutation rate, rearrangements and gene losses (Cai et al 2008;Magee et al 2010). In general, chloroplasts have sufficient ribosomal RNA (rRNA) and transporter RNA (tRNA) genes to compose the translation machinery for expression of their own genes (Wicke et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…otophora (Asaf et al, 2016). In all the species of Nicotiana, the LSC region contained a greater amount of SSRs in comparison to SSC and IR, which has also been demonstrated in other studies of angiosperm plastid genomes ( Asaf et al, 2016;Shahzadi et al, 2019;Mehmood et al, 2019, Yang et al, 2019. To understand molecular evolution, it is important to analyze nucleotide substitution rates (Muse & Gaut, 1994); in plastid genomes LSC and SSC regions are more prone to substitutions and indels, whereas the IRs are more conserved (Ahmed et al, 2012;Abdullah et al, 2019b).…”
Section: Molecular Evolution Of Nicotiana Plastid Genomesmentioning
confidence: 72%